Numerical and experimental studies of the plasma-thermal processing of ash and slag waste - Messerle, V.Е.; Lavrichshev, O.A.; Ustimenko, А.B. (Recent Contributions to Physics, 2023)
This paper presents the results of thermodynamic and experimental studies of plasma-thermal processing of ash with the production of fuel gas and inert mineral material are presented. Plasma-thermal processing of ash and slag wastes consists in their heating, pyrolysis and melting to remove residual carbon and obtain a neutral melt, the storage and use of which after cooling does not cause environmental problems. Ash from Ekibastuz coal, which is widely used in the energy sector of Kazakhstan, is taken as ash and slag waste, which is a set of components of the mineral mass of coal and unburned carbon. Calculations have shown that during the plasma-thermal processing of ash and slag waste, combustible gas is obtained with a CO concentration of up to 86.8% and a calorific value of 8752 kJ/kg and a melt of mineral components that does not contain harmful impurities. The plasma reactor is a melting chamber covered by an electromagnetic coil. The chamber has the shape of an equilateral triangle in section, with three inclined immersed graphite electrodes at its corners. The reactor was started up by shorting the power electrodes to a bulk graphite track. After obtaining the melt channel, the heating of ash and slag waste continues due to the conduction currents between the power electrodes through the resulting melt. To homogenize the melt, it is stirred electromagnetically. The melt productivity of the reactor was 100 kg/h at its temperature of 1923 K and specific energy consumption of 0.96 kW h/kg. Both in calculations and in experiments, no harmful impurities were found in the products of plasma processing of the investigated wastes.